Pendidikan Lingkungan untuk Siswa Sekolah Dasar di Pesisir Kecamatan Kasemen, Kota Serang, Banten - Daniel Julianto Tarigan; Agung Setyo Sasongko; Himawan Prasetiyo; Deri Hendriawan; Muhammad Nurshalim; Aang Fuad Hasan; Narpati Zayni Khalis; Deri Hendriawan (Jurnal Pengabdian Masyarakat PGSD, 2021)
The purpose of this community service is to provide an understanding about the coastal environment to students of State Elementary School of Kebon, Kasemen District, Serang City. The method used in this community service is by providing teaching and socialization about protecting the environment in coastal areas. This community service is intended due to students of State Elementary School of Kebon live in direct contact with the coastal area. The teaching and socialization were conducted from September to November 2020. The teaching is conducted online through WhatsApp groups since the local and school policies did not allow face-to-face learning. Participants in this community service program were 50 students from grades 5 and 6. The conclusion is that through this program students of State Elementary School of Kebon become more aware and care about their coastal environment. This early environmental education is expected to reduce the behavior of disposing of trash inappropriately and increase students’ awareness of State Elementary School of Kebon to protect the coastal environment